Optimalisasi Sektor Agropolitan Provinsi Jawa Timur Sebagai Upaya Pemulihan Ekonomi Lokal Di Masa Pandemi Covid 19 - Putra, Langgeng Rachmatullah; Ilyas, Taufiq Rahman; Suyeno, Suyeno (Universitas 17 Agustus 1945 Surabaya, 2021)
Optimization of the agropolitan sector as an effort to recover the economy impact of the covid 19 pandemic is strategic step teken by the East Java Provincial Government. Empowerment of the agropolitan community is an option considering its position as the spearhead of agricultural commodities. All these actions must be carried out through the development of an efficient system. The research method used is literature study by compiling data, then analyzing data, and finally drawing conclusions. The conclusions for these strategic steps including the following ; 1) Maximizing of writted regulation in institusional strengthening in the agropolitan sector, 2) Expanding cooperation between local, central goverment, financial institution, BUMN, and all related group. 3) Product Diversification, 4) Marketing Education, 5) Digital Marketing, 6) Ease of acces to capital sector. Then the advice that can be given is that the government must be consistent in supporting and providing assistance to the agropolitan community in developing agropolitan areas for local economic recovery.